The Measurement of Protein in Powdered Milk Products and Infant Formulas: A Review and Recent Developments. (27th November 2019) - Elgar, Dave; Evers, Jaap M; Holroyd, Stephen E; Johnson, Richard; Rowan, Angela
Abstract: Proteins are a key nutritional component of both powdered milk and infant formula types of product, and reliable methods for their determination are important for manufacturing and international trade. In this review, we distinguish between methods used for determining protein quality for nutrition purposes and those used for determining chemically defined protein. The former methods cover the ability of a dietary protein source to meet human nutritional requirements for the indispensable amino acids. The latter are chemical methods for the determination of total protein and can be divided into three broad types: total nitrogen determination, direct protein determination, and indirect protein determination. Current techniques and recent developments in each are reviewed.